Investigation of the hydrodynamics in the regenerator of fluid catalytic cracking unit integrated by chemical looping combustion - Güleç, Fatih; Erdogan, Ahmet; Clough, Peter T.; Lester, Edward (Elsevier, 2021)
Oil refineries are responsible for 4–6% of global CO2 emissions, and 20–35% of these emissions released from the regenerator of Fluid Catalytic Cracking (FCC) units, which are the essential units for the conversion of heavier petroleum residues (vacuum gas oil) into more valuable products. Chemical looping combustion (CLC) has been recently proposed to mitigate the CO2 emissions released from the regenerator of FCC units with a lower energy penalty. However, a detailed experimental and modelling investigation is still necessary in order to identify the hydrodynamics in the regenerator of chemical looping combustion integrated with fluidised catalytic cracking (CLC-FCC). A computational fluid dynamic (CFD) study was conducted to understand the hydrodynamic behaviours of gas-solid two-phase flow in the regenerator of the CLC-FCC unit, based on a three-dimensional multiphase model (Eulerian-Eulerian) with the kinetic theory of granular flow. The results provide a useful insight into regenerator hydrodynamics, in terms of oxygen carrier modified FCC catalysts and FCC coke distribution profiles, in the regenerator of CLC-FCC. The conventional drag models (Syamlal-O'Brien and Gidaspow) predict a bed density profiles of a dense phase (250–300 kg/m3) at the dense phase (0–0.25 of h/H), and a dilution phase from h/H = 0.25 to 0.50 of regenerator. The bed density profile is indistinguishable from the industrial data provided for conventional FCC regenerators. The fluidisation gas (CO2) passes through the centre of the regenerator where the fluidisation gas splits the catalyst particles from the centre to the walls, to create a dilute particle phase in the centre and a dense particle-phase near the wall, which is one of the characteristic flow regimes in circulating fluidised bed reactors. The particles in the centre demonstrate an upward flow trend with a particle velocity above 3.0 m/s while the dense particles near the wall tend to go down with relatively low particle velocity of <0.5 m/s, which creates vortexes and a non-uniform particle distribution in the regenerator. The distribution of the fluidising gas provides better mixing of solid particles in the entrance and the optimisation of the superficial gas velocities (1.0 m/s) to create a distributed flow regime with developed vortexes through the dense and dilute phases. Furthermore, the laminar and turbulent flow models demonstrated no significant differences in terms of axial bed density profile in the regenerator of the CLC-FCC concept. These findings demonstrated that the hydrodynamics of catalysts in the CLC-FCC regenerator successfully predicted with CFD modelling and the prediction results aligned well with the conventional FCC regenerator.
Keywords: CO2 capture; CLC-FCC; Chemical looping combustion; Fluid catalytic cracking; CFD